Effect of periodontal therapy on maxillary sinus mucous membrane thickening in chronic periodontitis: A split-mouth study - Vrushali N. Lathiya; Abhay P. Kolte; Rajashri A. Kolte; Dhawal R. Mody (Tabriz University of Medical Sciences, 2018)
Background. This study evaluated the effect of periodontal therapy on mucous membrane thickening in maxillary sinus in chronic periodontitis patients using radiovisiography (RVG) and cone-beam computed tomography (CBCT). Methods. The study population included 30 patients diagnosed with chronic periodontitis, exhibiting bilateral mucosal thickening of maxillary sinus. The selected sites were randomly assigned to group I (control group - not receiving periodontal therapy) and group II (test group - receiving periodontal therapy). The clinical parameters and mucosal thickening of the maxillary sinus were evaluated at baseline and after 9 months. Results. There was a significant decrease in the PPD, CAL as well as mucosal thickening in group II while, group I showed an increase in these parameters. In group II at the end of 9 months the mean mucosal thickening reduction as assessed by CBCT was 0.76±0.18, 0.73±0.24, 0.88±0.42 and 1.13±0.43 mm at the most anterior point (AP), the most posterior point (PP), the mid-point (MP), point of maximum thickness (MT) as well as in the length of the thickened mucosal lining, respectively. Conclusion. The results of our study indicated a reduction in the mucosal thickening of the maxillary sinus after surgical periodontal therapy. The trial was registered with the Clinical Trial Registry of India (Trial REF/ 2016/02/010805).